44.3: Characterization of Intra‐molecular Energy Transfer in Reactive Mesogen Liquid Crystal Mixtures. Issue 1 (1st July 2013) - Hsieh, Chung‐Ching; Zhao, Youngchao; Song, Yanjun; Chiu, Chung‐Yi
Abstract The Polymer‐stabilized alignment method has highly potential for manufacturing high performance displays due to the higher contrast ratio and faster response. In this study, we have investigated the liquid crystal mixture with alkenyl group monomer for response and reliability issues. The alkenyl group monomer can help reducing the rotational viscosity but cause the residual of reactive mesogen (RM) increased. New RM was adopted to overcome the residual issue and contributed excellent optical and reliability results.